Optimal formulation of recycled polypropylene/rubberwood flour composites on hardness property - Ratanawilai, Thanate (Applied Mechanics and Materials, 2013)
Mixture experimental design was applied to determine the optimal mixture for composites between rubberwood flour (RWF) and recycled polypropylene (rPP). Experiments were conducted based on a D-optimal mixture design and analyzed using response surface methodology. Analysis of variance revealed that compositions including rPP, RWF, maleic anhydride grafted polypropylene (MAPP), and ultraviolet (UV) stabilizer significantly affected hardness property. Contour plots of the response surface demonstrated that an increase of RWF content steadily enhanced hardness value, but hardness property sharply decreased with an increase of rPP loading. An addition of the UV stabilizer in the composites showed a slight decrease of the hardness value. This result recommends that amount of UV stabilizer used should be minimized. With this experimental design, the optimal formulation of rPP/RWF composites found was 50.0 wt% rPP,45.0 wt% RWF, 3.9 wt% MAPP, 0.1 wt% UV stabilizer, and 1.0 wt% Lubricant.